Mechanism of large-scale reservoir landslides with double-sliding zones: insights from long-term field monitoring - Yang, Yuting; Zhang, Chenyang; Lu, Yushi; Dai, Zhenwei (Frontiers in Ecology and Evolution, 2024)
A significant number of ancient landslides with double or multi-sliding zones exist in reservoir areas. However, understanding large-scale reservoir landslides with double-sliding zones remains limited due to the challenges of studying deformation along the sliding zone independently from surface deformation. In this study, the seepage and deformation characteristics of the Taping landslide were obtained through field investigations and long-term in-situ monitoring. For the first time, hydrological factors influencing double-sliding zones were revealed using an attribute reduction algorithm based on long-term field data. The results indicate that the Taping landslide undergoes significant step-like consistent creep deformation, exhibiting failure along double-sliding zones. For the toe part, reservoir water level (RWL) and precipitation are two critical hydrological factors triggering deformation. Shallow sliding is more susceptible to rainfall, while the deep sliding zone is more affected by RWL variations. In the rear part, precipitation has a greater impact than RWL. Daily precipitation is the primary hydrological factor affecting slope movement along the shallow sliding zone. However, accumulated precipitation over the previous seven days is the most crucial factor influencing slope movement along the deep sliding zone. During the RWL drawdown period, shallow sliding initially occurs at the toe, induced by the de-buttressing effect, while deep sliding occurs after the RWL reaches 145 m, induced by the downslope seepage force. Local damage and failure at the toe provide space for the instability of the rear part, reducing the anti-sliding force.Consequently, failure extends to the rear part. The findings of this study hold significant implications for gaining a deeper understanding of the deformation mechanisms of large-scale reservoir landslides with double-sliding zones and improving landslide management and mitigation strategies in reservoir area.